Sistem Informasi Reservasi Hotel Pada GM. Marsaringar Balige Berbasis Android - Sitorus, S. Artaulina; Malau, Emerson Porman (MEANS (Media Informasi Analisa dan Sistem), 2017)
GM Hotels. Marsaringar Balige is a company engaged in hospitality services. During this time the reservation system at GM Hotels. Marsaringar Balige is still manual, such as booking rooms, recording guest data, and data from each part not yet integrated such as restaurant data, ballroom, karaoke, and making reports still using Microsoft Excel office applications. One effort to improve the quality of hospitality services at GMs. Marsaringar Balige is by utilizing information technology, namely by designing an Android-based Hotel Reservation Information System. Is the right solution to overcome the problems of hotel managerial data processing needs that are dynamic and can be accessed through websites or mobile devices. Mobile devices integrated with the web are one of the right choices for processing hotel information systems. A user / guest can get information by making a request from an application that was previously installed on an android smartphone to the database. All data exchange processes are stored on the web server. And the HotelGM Reservation Information System. Android-based Marsaringar Balige is built using the PHP programming language, Eclipse is supporting software for Android mobile, and Phpmyadmin as a tool for managing Mysql database, and Text editor using Macromedia Dreamweaver8.